Efektivitas Program Transmigrasi Kabupaten Sumedang - Rika Kusdinar; Fajar Fajarudin; Moch Prisma Triadi N.K; Nova Deviayanti Aini; Yusuf Maulana (LPPM UNSAP & FISIP UNSAP, 2022)
This study aims to identify, process data, analyze, and measure the effectiveness of the Transmigration program at the Manpower and Transmigration Office of Sumedang district. The method used in this research is a qualitative method or often referred to as the naturalistic method. A qualitative approach is a research procedure that produces descriptive data in the form of written or spoken words from observable people or actors. Data collection techniques were carried out through library research and field studies. Determination of informants in this study using purposive sampling technique, which is a sampling technique based on the needs of 4 people. Meanwhile, the research data processing procedure uses the Miles and Huberman Model data analysis technique which consists of data reduction, data presentation and conclusion drawing/verification. Based on the results of the research and discussion, researchers can draw the conclusion that the Effectiveness of the Transmigration Program at the Manpower and Transmigration Office of Sumedang Regency is going well, namely by achieving the goals of the Transmigration program to improve people's welfare in population distribution and reduce poverty. The suggestions for this research are to improve the facilities and infrastructure supporting the program, so that the implementers can work optimally.